Metabolism study for CUMYL‐4CN‐BINACA in human hepatocytes and authentic urine specimens: Free cyanide is formed during the main metabolic pathway. Issue 8 (16th April 2018) - Åstrand, Anna; Vikingsson, Svante; Lindstedt, Daniel; Thelander, Gunilla; Gréen, Henrik; Kronstrand, Robert; Wohlfarth, Ariane
Abstract: To further elucidate the metabolism of CUMYL‐4CN‐BINACA, a new synthetic cannabinoid with a cyano group, and to evaluate biomarkers, we incubated the substance in human hepatocytes and analysed 9 authentic urine specimens. We also quantified CUMYL‐4CN‐BINACA and cyanide in blood and provide comprehensive data on the 7 autopsy cases, 5 of them determined CUMYL‐4CN‐BINACA intoxications. For metabolite elucidation, CUMYL‐4CN‐BINACA was incubated with pooled human hepatocytes for up to 5 hours, urine samples were analysed with and without enzymatic hydrolysis. Data was acquired in data‐dependent mode by ultra‐high performance liquid chromatography–high resolution mass spectrometry (UHPLC–HRMS) with an Agilent 6550 QTOF. For quantitative analysis of CUMYL‐4CN‐BINACA, blood samples were precipitated and analysed by liquid chromatography–tandem mass spectrometry (LC–MS/MS). Cyanide was determined by gas chromatography–headspace–nitrogen phosphorus detection (GC–headspace–NPD). CUMYL‐4CN‐BINACA was metabolised via CYP450‐mediated hydroxylation at 4‐butyl position generating a cyanohydrin (M12), which releases free cyanide to form an aldehyde intermediate and eventually generates 4‐hydroxybutyl CUMYL‐BINACA (M11) and CUMYL‐BINACA butanoic acid (M10). Other minor metabolites were produced by hydroxylation, dihydroxylation, N‐dealkylation, and dihydrodiol formation; glucuronidation was observed. One urine sample showed high intensities of M10 and a wide variety of metabolites; the other samples contained fewer metabolites in low abundance and 1 sample showed no metabolites. CUMYL‐4CN‐BINACA blood concentrations ranged from 0.1 to 8.3 ng/g showing an overlap between fatal and non‐fatal concentrations. One blood sample contained 0.36 μg/g cyanide. Release of free cyanide during metabolism is worrying as it might induce liver toxicity. As suggested earlier, CUMYL‐BINACA butanoic acid is the most abundant biomarker in urine, but monitoring of additional metabolites or, even better, analysis for the parent in blood is recommended. Abstract : CUMYL‐4CN‐BINACA is primarily metabolized via a cyanohydrin, which forms an aldehyde intermediate and eventually generates 4‐hydroxybutyl CUMYL‐BINACA and CUMYL‐BINACA butanoic acid. Free cyanide might lead to liver toxicity.